2022
DOI: 10.3390/nu14194149
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of Equations to Estimate Resting Energy Expenditure in Critically Ill Children and Adolescents with and without Malnutrition: A Cross-Sectional Study

Abstract: We evaluated the validity of sixteen predictive energy expenditure equations for resting energy expenditure estimation (eREE) against measured resting energy expenditure using indirect calorimetry (REEIC) in 153 critically ill children. Predictive equations were included based on weight, height, sex, and age. The agreement between eREE and REEIC was analyzed using the Bland–Altman method. Precision was defined by the 95% limits of the agreement; differences > ±10% from REEIC were considered clinically unacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 54 publications
3
16
0
Order By: Relevance
“…The Schofield equation, with weight and height, showed the best performance for the entire group and subgroups according to age, sex, nutrition status, and organ failure. Among 16 tested equations in 153 children (median age: 7.5 years), 32 the majority, especially the Recommended Dietary Allowances, overestimated REE measured by E‐COVX. In contrast to the above findings, the Schofield weight and height equation overestimated REE with one of the highest bias, and the HB equations had a smaller bias but still had wide limits of agreement.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Schofield equation, with weight and height, showed the best performance for the entire group and subgroups according to age, sex, nutrition status, and organ failure. Among 16 tested equations in 153 children (median age: 7.5 years), 32 the majority, especially the Recommended Dietary Allowances, overestimated REE measured by E‐COVX. In contrast to the above findings, the Schofield weight and height equation overestimated REE with one of the highest bias, and the HB equations had a smaller bias but still had wide limits of agreement.…”
Section: Resultsmentioning
confidence: 99%
“…40 In terms of factors that may affect the accuracy of predictive equations, two recent studies, involving one-third of overweight or obese patients, showed that apart from age, inaccuracy of the equations was not correlated to factors such as the presence of overweight or obesity, diagnostic categories including trauma, or disease severity. 32,33 Factors impacting EE (subquestion 1c)…”
Section: Methods Of Estimation Of Ree (Subquestion 1b)mentioning
confidence: 99%
See 2 more Smart Citations
“…Our study has several limitations due to the retrospective analysis of prospectively and automatically collected data. Moreover, we assessed VO 2 via the PAC and did not use indirect calorimetry, which is known as the gold standard for measuring VO 2 , carbon dioxide production and resting energy expenditure [ 20 , 21 ]. Studies correlating VO 2 values measured via the PAC in comparison to indirect calorimetry remain outstanding.…”
Section: Discussionmentioning
confidence: 99%